化简求值:[(3x^2y^2+4)-(xy+2)(2-xy)]/(-4xy),其中x=-2,y=
1个回答
先化简为:
(3x^2y^2+4-x^2y^2-4)/(-4xy)
=2x^2y^2/(-4xy)
=-xy/2
x=-2,y=1/2
所以原式=1/2
相关问题
先化简,再求值:3x 2 y·(﹣4xy 2 )+5xy·(﹣2xy) 2 ,其中x=2,y= .
先化简再求值:3x2y-[2xy2-4([1/2]xy-[3/4]x2y)+xy]+3xy2,其中x=3,y=-1.
先化简再求值 2x²+xy/4x²+4xy+y²,其中x=-2,y=3
化简求值:-xy(x2y5-xy3-y),其中xy2=-2.
(-3xy-7y)+[4x-3(xy+y-2x)],其中xy=-2,x-y=3,先化简,再求值.
先化简再求值:4xy-[(x^2+5xy-y^2)-(x^2+3xy-2y^2)]其中x=1/4,y=1/2
化简求值:2(x2y+xy)-3(x2y-xy)-4x2y,其中x=-1,y=1.
化简求值:2(x2y+xy)-3(x2y-xy)-4x2y,其中x=-1,y=1.
化简求值: [(xy+2)(xy-2)-2x²y²+4]÷(xy), 其中x=20,y=- 1/25
化简求值3x²y-[2xy-2(xy-3/2x²y)+xy]+3xy²其中x=3、y=-1